2016
DOI: 10.1186/s13287-016-0363-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of mesenchymal stem/stromal cell function

Abstract: The past decade has seen an explosion of research directed toward better understanding of the mechanisms of mesenchymal stem/stromal cell (MSC) function during rescue and repair of injured organs and tissues. In addition to delineating cell–cell signaling and molecular controls for MSC differentiation, the field has made particular progress in defining several other mechanisms through which administered MSCs can promote tissue rescue/repair. These include: 1) paracrine activity that involves secretion of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
569
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 683 publications
(587 citation statements)
references
References 182 publications
5
569
0
13
Order By: Relevance
“…There is overwhelming evidence that MSC in their natural environment secrete both pro-and anti-inflammatory cytokines as well as their antagonists [51]. Such secretions triggered cellular communication circuitry and have been shown to provide sophisticated signaling guidance to many immune cells, including T cells, natural killer cells, B cells, monocytes, macrophages and dendritic cells [25,47,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…There is overwhelming evidence that MSC in their natural environment secrete both pro-and anti-inflammatory cytokines as well as their antagonists [51]. Such secretions triggered cellular communication circuitry and have been shown to provide sophisticated signaling guidance to many immune cells, including T cells, natural killer cells, B cells, monocytes, macrophages and dendritic cells [25,47,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In the implants, iPS-NCLC-MSCs expressed osteoblast marker genes, indicating that the cells could differentiate into osteoblasts and directly contribute to bone regeneration in vivo. Recent reports have also shown that adult MSCs have the capacity to secrete factors such as soluble extracellular matrix glycoprotein, cytokines, and growth factors to modulate the microenvironment and recruit resident cells to repair the degenerated tissue 40) . Thus, transplanted iPS-NCLC-MSCs in this study may also play a role in activating endogenous osteogenic progenitor cells by secretion of such factors.…”
Section: Gfp Osx Mergementioning
confidence: 99%
“…Hence, the pathological fate of the transplanted or mobilized MSCs does not only depend on the homeostasis of [Ca ] m in evading the stress phenotype for better differentiation and repair [39,40]. Many studies on the isolated mitochondria suggest that the Ca 2+ buffering capacity of mitochondria is 100-fold higher than the basal or resting [Ca 2+ ] i or intracellular release on the stimulation of Ca 2+ release in the cytoplasm [41][42][43]. This phenomenon is observed during the physiological stress arising due to ischemia or reperfusion and can be experimentally induced with a known Ca 2+ agonist like histamine or thapsigargin.…”
Section: Mesenchymal Stem Cells React Differently To Stress Pathologymentioning
confidence: 99%